Bangunan Lembaga Hasil Dalam Negeri, Kompleks Kerajaan Jalan Tuanku Abdul Halim, 50600 Kuala Lumpur / Nurdiana Ellysha Azman ... [et al.] - Nurdiana Ellysha, Azman; Husna Syahidah, Zainordin; Nur Amira Shuhada, Alias; Muhammad Fariz Azri, Ab Rahim (2019)
Lembaga Hasil Dalam Negeri Malaysia Malaysia (LHDNM) or The Inland Revenue Board of Malaysia (IRBM) is one of the main agencies under the Ministry of Finance who is responsible for collecting and administering the state's direct taxes. IRBM or LHDN was established in accordance with the Inland Revenue Board of Malaysia Act 1995 to give it more autonomy especially in financial and personnel management as well as to improve the quality and effectiveness of tax administration. Planning and scheduling is one of the fastest and most effective investments for this organization make to improve productivity and availability. The building maintenance planning in this building using well-functioning maintenance organization and scheduling to work many other systems to work well. Most importantly equipment inspections through preventive maintenance, technical database such as bill of materials, work order history, and standard job plans. Maintenance spare part stores is function well.